Evaluation of the sports learning program phase C in the West Air Hangat sub-district based on CIPP - Wafil Dawami; Arsil Arsil; Roma Irawan; Nugroho Susanto (JETL (Journal of Education, Teaching and Learning), 2025)
This study aims to evaluate the Physical Education, Sports, and Health Phase C learning program in Air Hangat Barat District using the CIPP (Context, Input, Process, Product) evaluation model. This evaluation was conducted to assess the program's suitability to the needs of students, the availability of infrastructure, the implementation of the learning process, and the learning outcomes achieved. The research method used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation studies. The research subjects included PJOK teachers and principals in 4 elementary schools in the Air Hangat Barat District. The results of the Context evaluation showed that the PJOK Phase C program was by the curriculum but needed adjustments to student characteristics. In the Input aspect, it was found that sports facilities were still limited and needed to improve teacher qualifications. The Process evaluation revealed that the learning methods were varied, but needed to be strengthened in the use of media and authentic assessment. Meanwhile, the Product evaluation showed that most students achieved basic competencies, but needed improvement in aspects of psychomotor skills and sportsmanship. This study concludes that the Phase C Physical Education (PJOK) learning program in Air Hangat Barat District has been running quite well, but requires improvements in facilities, teacher development, and the approach to evaluating learning outcomes. Recommendations include increasing the budget for infrastructure, teacher training, and implementing more innovative learning models